2017
DOI: 10.1002/cncr.30597
|View full text |Cite
|
Sign up to set email alerts
|

Future of testicular germ cell tumor incidence in the United States: Forecast through 2026

Abstract: Background Testicular germ cell tumors (TGCT) are rare tumors in the general population but are the most commonly occurring malignancy among men between ages 15 and 44 years in the United States (US). While non-Hispanic whites (NHW) have the highest incidence in the US, rates among Hispanics have shown the greatest increase in recent years. To forecast what these incidence rates may be in the future, an analysis of TGCT incidence in the Surveillance, Epidemiology, and End Results Program, and National Program … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
80
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(82 citation statements)
references
References 52 publications
0
80
1
1
Order By: Relevance
“…Ghazarian et al . showed in their study that ethnical differences also exist within the United States: High incidence rates are present in the white population (non‐Hispanic), but the strongest increase in TGCT was observed in the Hispanic population (Ghazarian et al ., , ). Aside from these studies, an increase in incidence rates is frequently reported throughout literature with seminoma being more common than non‐seminoma (Zheng et al ., ; Richiardi et al ., ; Chia et al ., ; Ghazarian et al ., ; Smith et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Ghazarian et al . showed in their study that ethnical differences also exist within the United States: High incidence rates are present in the white population (non‐Hispanic), but the strongest increase in TGCT was observed in the Hispanic population (Ghazarian et al ., , ). Aside from these studies, an increase in incidence rates is frequently reported throughout literature with seminoma being more common than non‐seminoma (Zheng et al ., ; Richiardi et al ., ; Chia et al ., ; Ghazarian et al ., ; Smith et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Testicular cancer, including germ cell, Sertoli cell, and Leydig cell tumors, is one of the most common solid tumors in men between 15 and 44 years of age with about 9310 new cases found in the United States annually . Chemotherapy with or without surgery and/or radiotherapy combination is an important therapeutic strategy for testicular cancers .…”
Section: Introductionmentioning
confidence: 99%
“…Testicular cancer, including germ cell, Sertoli cell, and Leydig cell tumors, is one of the most common solid tumors in men between 15 and 44 years of age with about 9310 new cases found in the United States annually. 1,2 Chemotherapy with or without surgery and/or radiotherapy combination is an important therapeutic strategy for testicular cancers. 3,4 However, the clinical applications of chemotherapy are limited because of severe side effects, such as cardiovascular diseases and respiratory infections, which lead to a 6% increased risks of noncancer death in long-term testicular cancer survivors after treatments with chemotherapy and/or radiotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…While our understanding of the most effective treatments for TGCT – even advanced disease – have led to dramatic increases in survival (Trama et al ., ), key aspects of TGCT remain a mystery. Firstly, in general rates of TGCT appear to be increasing steadily over time: (Sincic et al ., ; Le Cornet et al ., ; Znaor et al ., ; Trabert et al ., ; Ghazarian et al ., ; Ministry of Health, ) for example, rates in the United States have been steadily increasing for decades and are projected to continue to do so (Ghazarian et al ., ), while in New Zealand (NZ) the national rate of TGCT has increased from around 2 cases/100,000 males in 1950 to around 8 cases/100,000 males in 2015 (Fig. ) (Ministry of Health, ).…”
Section: Introductionmentioning
confidence: 99%